2019
DOI: 10.1021/acs.jpcb.9b04354
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Base-Specific Dynamics during Melting of DNA–Ligand Complexes Using Temperature-Jump Time-Resolved Infrared Spectroscopy

Abstract: Ultrafast time-resolved infrared spectroscopy employing nanosecond temperature-jump initiation has been used to study the melting of double-stranded (ds)DNA oligomers in the presence and absence of minor groovebinding ligand Hoechst 33258. Ligand binding to ds(5′-GCAAATTTCC-3′), which binds Hoechst 33258 in the central A-tract region with nanomolar affinity, causes a dramatic increase in the timescales for strand melting from 30 to ∼250 μs. Ligand binding also suppresses premelting disruption of the dsDNA stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(74 citation statements)
references
References 50 publications
3
70
0
Order By: Relevance
“…Both the A ring mode at 1622 cm −1 and the G ring modes at 1540-1580 cm −1 increase in intensity with the loss of base-pair stacking. The IR spectra of H-DNA show much smaller changes compared to native DNA over the same temperature range, indicating a strong stabilization effect to the duplex upon H binding 30,31 . To describe the global spectral changes that occur with thermal dissociation, we analyzed the temperaturedependent IR spectra using single value decomposition (SVD).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Both the A ring mode at 1622 cm −1 and the G ring modes at 1540-1580 cm −1 increase in intensity with the loss of base-pair stacking. The IR spectra of H-DNA show much smaller changes compared to native DNA over the same temperature range, indicating a strong stabilization effect to the duplex upon H binding 30,31 . To describe the global spectral changes that occur with thermal dissociation, we analyzed the temperaturedependent IR spectra using single value decomposition (SVD).…”
Section: Resultsmentioning
confidence: 97%
“…Although the fraying of the terminal G:C base pairs has been previously observed in both native and H-DNA 25,30 , the effect of ligand binding on this process is elusive. Recently, Fritzsch et al 31 reported a dissociation kinetics study of H bound to similar duplexes that vary in their central AT sequences using T-jump IR spectroscopy, finding that the ligand's impact on fraying is correlated with its binding affinity. As with our results, they observed that H binding suppressed the short time dissociation response (~100 ns) from A ring modes.…”
Section: Dissociation Of H-dna Observed By T-jump Irmentioning
confidence: 99%
See 1 more Smart Citation
“…Transient changes in the IR spectra of ODNs caused by a temperature jump initiated by high energy laser pulses have been reported recently by Hunt and co-workers. 20 These researchers observed that the temperature jump could cause melting or pre-melting of the ODN. However, the kinetics reported are quite different from what is observed in our studies.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important temporal window, as it has been shown that small peptides and nucleic acid sequences undergo changes in secondary structure on microsecond timescales that are preceded by structural fluctuations, for example end fraying of helices on sub-microsecond timescales. 811 In studies of large protein systems, it has been shown that the response to T-jump initiation includes a fast downhill “burst phase” unfolding event that is followed by slower thermal unfolding. 7 It is argued that the fast initial response to the T-jump is instructive in understanding the roots of the unfolding mechanisms.…”
Section: Introductionmentioning
confidence: 99%